2019
DOI: 10.1111/jvim.15432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of duodenal perfusion by contrast‐enhanced ultrasonography in dogs with chronic inflammatory enteropathy and intestinal lymphoma

Abstract: Background Contrast‐enhanced ultrasonography (CEUS) can be used to evaluate intestinal perfusion in healthy dogs. It is helpful for diagnosing and monitoring inflammatory bowel disease in humans and could be useful for dogs with chronic intestinal diseases. Objectives To examine duodenal perfusion in dogs with chronic inflammatory enteropathy (CIE) and intestinal lymphoma. Animals Client‐owned dogs with CIE (n = 26) or intestinal lymphoma (n = 7) and dogs with gastrointestinal signs but histopathologically nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 42 publications
4
17
1
1
Order By: Relevance
“…In the case of granulomatous colitis, the mucosa and submucosa are known to be the more affected layers [ 1 ]. Furthermore, a rapid wash-in and gradual wash-out pattern was detected in our patient, similar to that described for the duodenum (in the normal, inflammatory, and neoplastic groups) [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the case of granulomatous colitis, the mucosa and submucosa are known to be the more affected layers [ 1 ]. Furthermore, a rapid wash-in and gradual wash-out pattern was detected in our patient, similar to that described for the duodenum (in the normal, inflammatory, and neoplastic groups) [ 17 ].…”
Section: Discussionsupporting
confidence: 86%
“…The distribution of the vessels in inflammatory lesions is reported to have a typical “comb-teeth-like” distribution, but in some cases of severe inflammation, this feature is no longer distinguishable [ 12 ]. The CEUS enhancement seen in this case reflects the described enhancement of the duodenum in dogs with IBD and lymphoma [ 17 ]. The outer layer in our case and the muscularis in the study of Nisa et al were markedly less enhanced than the mucosa.…”
Section: Discussionsupporting
confidence: 73%
“…One study reported that intestinal lymphoma may be present in bowel with normal or minimal alteration in wall thickness (highly variable with approximately equal numbers in the normal to mild, moderate and severe categories) and layering (20% of the patient retained normal wall layering), suggesting that distortion of wall layering and thickness are poorly sensitive for the diagnosis of lymphoma also in dogs and 4 patients with histopathologically confirmed lymphoma showed no sonographic alterations (Frances et al, 2013). One study examined duodenal perfusion using Contrast-Enhanced Ultrasonography (CEUS) in dogs with chronic inflammatory enteropathy (n = 26 dogs classified into: 16 Remission and 10 symptomatic based on clinical scores), intestinal lymphoma (n = 7 dogs) and a control group with GI signs but histopathologically normal duodenum (n = 14) showing no significant differences in perfusion parameters between the lymphoma and inflammatory groups or the lymphoma and control groups (Nisa et al, 2019). Ultimately, the optimal approach to diagnose GI lymphoma varies among clinicians: Fine-needle aspiration and cytology of intestinal masses and enlarged mesenteric lymph nodes are relatively non-invasive and rapid diagnostic methods.…”
Section: Intestinementioning
confidence: 99%
“…Contrast-enhanced ultrasonography (CEUS) is an imaging modality that could improve the diagnostic accuracy of standard US: the use of intravascular contrast medium (CM), like the second-generation ones, may improve the visualization of blood perfusion and microvascular architecture, allowing qualitative and quantitative vascular assessment of various organs in both physiological and pathological conditions in dogs and cats [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, CEUS has proved to be an extremely safe and well-tolerated technique [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CEUS has proved to be an extremely safe and well-tolerated technique [ 31 ]. In veterinary medicine, several studies have described the usefulness of this modality in the characterization of inflammatory and neoplastic diseases [ 16 , 18 , 19 , 21 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 32 ]. However, regarding the stomach, only one study has been conducted to investigate the reliability of low-mechanical index imaging compered to Doppler flowmetry for the assessment of gastric mucosal blood flow in healthy dogs, demonstrating the feasibility of CEUS quantitative evaluation in this organ [ 33 ].…”
Section: Introductionmentioning
confidence: 99%